2019
DOI: 10.1021/acs.chemmater.9b01141
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Phase Infiltration of Metal Oxides into Nanoporous Polymers for Organic Solvent Separation Membranes

Abstract: Membrane-based organic solvent separations promise a low-energy alternative to traditional thermal separations but require materials that operate reliably in chemically aggressive environments. While inorganic membranes can withstand demanding conditions, they are costly and difficult to scale. Polymeric membranes, such as polymer of intrinsic microporosity 1 (PIM-1), are easily manufactured into forms consistent with large-scale separations (e.g., hollow fibers) but perform poorly in aggressive solvents. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 56 publications
4
118
1
Order By: Relevance
“…The method of combining SIS of organometallic precursors into polymers with LIG formation described in this paper can be generalized to other applications where maintaining micro and nano-sized features of polymers at temperatures well above their T g is desired. An even broader advantage of this approach is the improved mechanical and chemical properties that are observed at these high temperatures, without the need to change the chemistry of the underlying polymer 28 . Other modification approaches that could potentially be used, such as crosslinking of the polymer, would alter the polymer chemistry, potentially altering the material's LIG forming properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of combining SIS of organometallic precursors into polymers with LIG formation described in this paper can be generalized to other applications where maintaining micro and nano-sized features of polymers at temperatures well above their T g is desired. An even broader advantage of this approach is the improved mechanical and chemical properties that are observed at these high temperatures, without the need to change the chemistry of the underlying polymer 28 . Other modification approaches that could potentially be used, such as crosslinking of the polymer, would alter the polymer chemistry, potentially altering the material's LIG forming properties.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to atomic layer deposition (ALD), SIS involves the sequential exposure of a material to alternating vapors of a reactive organometallic precursor and a counter reactant 24,25 . While ALD is performed on a non-porous substrate to grow inorganic films 26 , SIS is performed on polymers, where the diffusion of reactants into the polymer can change its chemical and mechanical properties, increasing its tensile strength 27 , changing its permeability to certain molecules 28 , improving its conductivity 29 , or allowing it to maintain its structure during annealing [30][31][32][33] . ALD, and similar techniques like SIS, have been widely and safely used for decades, both in industry and academic research 34 .…”
mentioning
confidence: 99%
“…Note that the glass transition temperature for this polymer is around À64 1C. 18 Vapor phase infiltration (VPI) of the polymer films was performed in a custom-built system described earlier, 15 and was controlled via a tree-based control software. 19 The chamber was operated at a temperature of 60, 80, or 100 1C.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to increase chemical stability of polymers in solvents by VPI has been reported for different systems. 8,15 In a recent study by McGuinness et al, 8 the stability of AlO x -poly(methyl methacrylate) hybrid films was tested in various solvents. The authors found that the infiltration temperature controlled the physicochemical structure of the final hybrid material and its resultant chemical dissolution performance.…”
Section: F Dissolution Of Zno-polyisoprene Hybrid Filmsmentioning
confidence: 99%
See 1 more Smart Citation